Retsstat, magtstat og suverænstat: Terrorlovgivninger i perspektiv - Niels Mandøe Glæsner (Danish Institute for International Studies (DIIS), 2010)
This study takes off by demonstrating how the ability of the state to define the difference between ordinary crime and terrorism, both historically and conceptually, is rootet in an immanent power reserve, which the sovereign state carries within from its founding. The paper links this power reserve, ultimately based on violence in the state of emergency, with the juridical language of the sovereign state. After drawing up this theoretical framework for the state's monopoly of the legal definition - based foremost on the thoughts of Carl Schmitt and Walter Benjamin - the paper thoroughly maps the legal anti terrorism measures taken in UK and Denmark. Through this study it is shown how to understand the unspecific language used in the anti terror laws, of a way of managing the state's monopoly of definition in the light of the threat of terrorism.
Keywords: 330; Staatstheorie; Politische Gewalt; Nationale Sicherheit; Innere Sicherheit; Dänemark